Potential Inaccuracies in Chloride Measurements in Patients with Severe Metabolic Acidosis - Tetsuya Makiishi; Naomasa Nishimura; Keiko Yoshioka; Shinya Yamamoto; Ryuichi Mitsuhashi; Sayako Maeda; Takashi Konishi; Kunihiko Hirose (International Journal of Nephrology)
Background. To address the cause(s) of the significant differences in chloride (Cl-) concentrations between point-of-care blood gas analyzers and central laboratory analyzers. Methods. Cl- concentrations measured simultaneously by a blood gas analyzer (ABL800 FLEX) and a central laboratory analyzer (Hitachi7600) were collected in patients with severe acidemia (pH<7.20) (n=32) and were examined for correlations between differences in Cl- and factors associated with the acid-base status. Cl- concentrations were measured with both analyzers for samples with different concentrations of lactate, inorganic phosphate, or bicarbonate (HCO3   −). Results. The differences in Cl- concentrations were correlated with HCO3   − concentrations (r=0.72, P<0.0001) and anion gap (r=0.69, P<0.0001). Only the addition of HCO3   − proportionately increased Cl- levels measured by a Hitachi7600, but it did not affect those measured by an ABL800FLEX. Conclusion. Cl- measurements with some analyzers may be influenced by HCO3   − concentrations, which could result in the observed discrepancies.